Competitive Variety Testing of winter common wheat in the conditions of the Penza region - S. V. Kosenko (Зерновое хозяйство России, 2023)
The current paper has presented the results of winter common wheat, studied in the nursery of the Competitive Variety Testing in the forest-steppe zone of the Penza region for 2016–2020. The purpose of the study was to estimate breeding lines of winter common wheat of the Competitive Variety Testing according to the main economic and biological traits and to identify samples with a complex of economically valuable traits and properties, in which the productivity level is stably maintained. The objects of the study were 35 winter common wheat lines developed by the FSBSI “Federal Research Center of Fiber Crops”. The zoned variety of winter common wheat ‘Fotinya’ was used as a standard one. The productivity of winter common wheat lines in the competitive variety testing ranged from 4.31 t/ha (the line ‘Erythrospermum 17/01-1-08’) to 4.85 t/ha (the line ‘Erythrospermum 12/00-16-04’). According to productivity, the standard variety ‘Fotinya’ significantly exceeded 13 lines, the increase of which ranged from 0.37 to 0.92 t/ha, НСР05 = 0.24 t/ha. During the study period, there was carried out a comprehensive estimation of winter common wheat lines to identify the best of them as carriers of economically valuable traits, which can promote developing new highly productive varieties with a high level of adaptability to the conditions of the forest-steppe of the Middle Volga region. The lines ‘Erythrospermum 12/00-16-04’, ‘Erythrospermum 29/03-2-06’, ‘Erythrospermum 21/00-3-08’, ‘Erythrospermum 18/04-3-08’, ‘Erythrospermum 17/01-7-08’ are of great interest for breeding, since they have been distinguished by a set of indicators (with a mean yield of 4.38–4.85 t/ha, more than 90 % of winter resistance, early maturity, 9 points of resistance to lodging, natural grain weight of 767–780 g/l, 86–90 % of kernel hardiness, 28.2–32.2 % of gluten in grain, 14.8–17.1 % of protein in grain). The selected lines have been recommended for inclusion in breeding programs for the development of highly productive winter common wheat genotypes.